Body mass index and use and costs of primary care services among women aged 55 to 79 years in England: a cohort and linked data study - Kent, S; Jebb, S; Gray, A; Green, J; Reeves, G; Beral, V; Mihaylova, B; Cairns, B; Million Women Study collaborators (Springer Nature, 2018)
Background Excess weight is associated with poor health and increased healthcare costs. There are no reliable data describing the association between BMI and the use and costs of primary care services in the United Kingdom. Methods Among 69,440 participants in the Million Women Study with primary care records in the Clinical Practice Research Datalink between April 2006 (mean age 64 years) and March 2014, the annual rates and costs of their primary care consultations, prescription medications, and diagnostic and monitoring tests were estimated in relation to their body-mass index (BMI) at recruitment in 1996-2001 (mean age 56 years). Associations of BMI with annual costs were projected to all women in England aged 55-79 years in 2013. Results Over an average follow-up of 6.0 years, annual rates and mean costs were lowest for women with a BMI of 20 to <22.5kg/m2 for consultations (7.0 consultations, 99% CI 6.8-7.1; £288, £280-£295) and prescription medications (27.0 prescribed items, 26.0-27.9; £227, £216- £237). Every 2kg/m2 higher BMI beyond 20kg/m2 (a 5kg change in weight for a woman of average height) was associated with 5.2% (4.8-5.6) and 9.9% (9.2-10.6) higher mean annual consultation and prescription medication costs, respectively. Annual rates and mean costs of diagnostic and monitoring tests were similar for women with different BMIs. Among all women aged 55-79 years in England, excess weight accounted for an estimated 11% (£229million/£2.2billion) of all consultation costs and 20% (£384million/£1.9billion) of all prescription medication costs, of which 27% were for diabetes drugs, 19% for circulatory system drugs, and 13% for analgesics. Conclusions Excess body weight is associated with higher use and costs of primary care services among women in England. Reducing the prevalence of excess weight could reduce pressures on primary care.